Collaborative Learning in Technical & Vocational Education and Training: A Mixed-Methods Quasi-Experimental Study in Chile - Sagredo-Gallardo, Miguel; González-Campos, José (Journal of Technical Education and Training, 2025)
This study assessed the impact of a structured Collaborative Learning intervention among a cohort of female students enrolled in a short-cycle Technical & Vocational Education and Training (TVET) program in Chile. Using a quasi-experimental, mixed-methods design, 37 participants were assigned to experimental and control groups. Quantitative data were collected using a locally adapted Cooperative Learning Questionnaire, providing preliminary evidence of reliability and supporting a five-factor structure. The intervention led to statistically significant, substantial pre–post gains in social skills, group processing, and promotive interaction, with positive but non-significant trends in positive interdependence and individual accountability. Thematic qualitative analysis identified gains in communication, empathy, teamwork, leadership, and conflict management, alongside greater professional readiness. These findings empirically support the integration of collaborative learning into TVET curricula and underscore the need for targeted faculty development and curricular innovation. However, the exclusive focus on a single cohort of female students and the brief intervention period limit generalizability. Further research is needed to examine scalability, gender dynamics, and digitalization in more diverse technical education contexts worldwide.